793 Orthopaedic Surgical Training in The Independent Sector During the COVID 19 Pandemic. (12th October 2021) - O'Callaghan, J; Lochab, S; Stanier, P; Woods, D
Abstract: Introduction: The COVID pandemic had led to the cancellation of elective Orthopaedics in the NHS. The aim of this study was to investigate the effect of the independent sector on orthopaedic training and the effect of the COVID pandemic on training locally. Method: A retrospective review of trauma and elective operations was made between April and September of 2019 and 2020 to compare the effects of COVID on training opportunities and the additional capacity provided by the private sector. Results: The impact of COVID on Surgical training at GWH has been no decrease in trauma operating experience, but a 53% decrease in elective operating experience and a 74% decrease in joint replacement operative experience during an equivalent six-month period. Use of the independent hospital has enabled 6% of the total elective surgery experience, and 11% of the joint replacement surgery experience. Discussion: The private sector has provided additional capacity but a productivity of 66 cases from 48 half day lists is low (1.4 cases per list) has proved disappointing. There has been a low impact on elective training. The challenges have been faced on the elective side as trauma cases have remained consistent during the pandemic. Conclusions: Use of the alliance between the private sector and NHS as a resource to provide additional training opportunities needs to be developed further in the future with incentivised guidance. Orthopaedic training will inevitably adapt to the challenges presented for the next generations of surgeons.